Vasculogenesis drives pulmonary vascular growth in the developing chick embryo - Anderson-Berry, A.; O'Brien, E.A.; Bleyl, S.B.; Lawson, A.; Gundersen, N.; Ryssman, D.; Sweeley, J.; Dahl, M.J.; Drake, C.J.; Schoenwolf, G.C.; Albertine, K.H. (Developmental Dynamics, 2005)
Formation of the pulmonary vasculature has been described as occurring by outgrowth of existing vessels (angiogenesis), de novo formation of new vessels (vasculogenesis), or a combination of both processes. Uncertainty about the contribution of angiogenesis and vasculogenesis to pulmonary vascular formation is partly due to methodologic approaches. Evidence in favor of angiogenesis stems from studies that used vascular-filling methods. Such methods identify only directly continuous lumina. Evidence for vasculogenesis has been provided by the use of molecular markers of blood vessel endothelium. Use of both methods has not been combined in the same species, however. We hypothesized, based on published evidence from quail and mouse, that chick pulmonary vascular formation occurs by vasculogenesis. To test that hypothesis, we used vascular filling, serial section, and immunohistochemical methods to analyze the developing lungs of chick embryos from Hamburger and Hamilton stages 20 to 43. Vascular filling suggested that the lumen of the pulmonary arteries sprouted from the sixth pharyngeal arch arteries. However, serial sections and immunohistochemical localization of fetal liver kinase-1 protein, the receptor for vascular endothelial growth factor, showed that the pulmonary arterial tree formed from endothelial cell precursors and coalescence of isolated blood vessels in the mediastinal splanchnic mesenchyme centrally to the developing lung tissue distally. Pulmonary veins grew from the left atrium to the developing lungs. Pulmonary blood vessel formation occurred continuously throughout the embryonic period studied. Our results show that vasculogenesis is the main process by which the pulmonary vasculature forms in the developing chick embryo. © 2005 Wiley-Liss, Inc.
Keywords: Blood vessel formation; Lung development; Receptor tyrosine kinases